Electron-ion-plasma modification of a hypoeutectoid Al-Si alloy - Zaguliaev, Dmitrii; Gromov, Victor; Konovalov, S. V. (Sergey Valerʹevich); Ivanov, Yu. F. (Yurii Fedorovich) (Boca Raton : CRC Press, 2021)
Electron-Ion-Plasma Modification of a Hypereutectic Al-Si Alloy details theoretical and experimental research and computer simulation of structural phase transformations in AlSi10Mn2Ni Silumin on different scale levels under electroexplosion alloying, electron beam processing and electron-plasma alloying at the nanolevel in order to create new materials. The authors summarize and analyze more than 10 years of research on the electron-ion-plasma effect on strength properties and structure-phase states' transformations of hypoeutectic Silumin. Key Features: Details physical and mathematical models of mechanisms of surface layer hardening under conditions of varying energy effects Offers insights into improved strength characteristics of Silumin Explores optimal processing modes for increased strength and improved tribological characteristics This book is a valuable resource to researchers and engineers involved with the modification of light alloy surfaces for the automotive and aeronautical industry.
OCLC-licensed vendor bibliographic record.
Keywords: Aluminum alloys -- Properties; Alloys -- Effect of radiation on; Electron beams; Ion bombardment; TECHNOLOGY / Metallurgy; TECHNOLOGY / Material Science; SCIENCE / Solid State Physics